Pengolahan Sistem Informasi Status Gizi Buruk Pada Puskesmas Kota Manna - Henokh Holian Saputra; Asnawati Asnawati; Ricky Zulfiandry (Jurnal Media Computer Science, 2026)
Community Health Centers (Puskesmas) play a crucial role in delivering primary health services, including the monitoring and management of malnutrition. Malnutrition remains a critical issue affecting child health and development, especially in vulnerable regions. This study aims to design and implement a web-based Malnutrition Information System at Puskesmas Kota Manna to improve the efficiency and accuracy of nutrition data management. The system is developed using the Waterfall methodology and utilizes PHP and MySQL as core technologies. Through this system, data recording, reporting, and analysis of malnutrition cases are carried out in a more structured and integrated manner. The implementation results show that the system helps healthcare workers monitor child nutritional status, accelerate decision-making processes, and reduce data entry errors. The study recommends user training and infrastructure improvement to ensure the system's optimal adoption across various healthcare areas.